2010
DOI: 10.1111/j.1469-8749.2010.03647.x
|View full text |Cite
|
Sign up to set email alerts
|

The neurology of coeliac disease in childhood: what is the evidence? A systematic review and meta‐analysis

Abstract: METHOD We conducted a review of paediatric studies published in English assessing neurological illness in coeliac disease identified through a MEDLINE search ). Calculation of computed relative risk, odds ratio, and risk difference was performed using the fixed effect method if applicable.RESULTS Fifteen studies were analysed (11 772 participants). The meta-analysis showed that (1) the relative risk of epilepsy in individuals with coeliac disease, and of coeliac disease in individuals with epilepsy, compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1
12

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 29 publications
(70 reference statements)
1
64
1
12
Order By: Relevance
“…It is also found at an increased rate in people with other auto-immune disorders, particularly type 1 diabetes mellitus (Triolo et al 2011) and in a variety of neurological conditions (Lionette et al 2010) .…”
Section: Diagnosis and Assessmentmentioning
confidence: 98%
“…It is also found at an increased rate in people with other auto-immune disorders, particularly type 1 diabetes mellitus (Triolo et al 2011) and in a variety of neurological conditions (Lionette et al 2010) .…”
Section: Diagnosis and Assessmentmentioning
confidence: 98%
“…Neurological presentations are also possible, sometimes in the absence of gastrointestinal symptoms. Neurological symptoms reported in CD include hypotonia, developmental delay, seizure disorders, learning disorders, ADHD, headache, cerebellar ataxia, peripheral neuropathy and rarely, tics (2,3). A study of approximately 300 children noted that 50% of children with CD had neurological symptoms, compared with 20% of controls (2).…”
Section: Diagnosis: Celiac Disease (Cd)mentioning
confidence: 99%
“…A meta-analysis of 15 studies [59] found a 2.1-fold increased risk of epilepsy in children with CD. However, recent data are less consistent and vary below these figures due to operational definitions of epilepsy [60].…”
Section: Epilepsymentioning
confidence: 99%
“…Zelnik et al [32] found that headache was the most common neurologic disorder (27.9%) in a group of 111 CD patients. A meta-analysis of 15 studies [59] found a 3.2-fold increase risk of headache in children with CD. Adherence to a gluten-free diet has been shown to have favorable outcomes on headache symptoms reported in CD [32,49,63].…”
Section: Headachementioning
confidence: 99%